2019
DOI: 10.3390/molecules24081512
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Volatiles of 15 Brands of Extra-Virgin Olive Oils Using Solid-Phase Micro-Extraction and Solvent-Assisted Flavor Evaporation

Abstract: Aroma profiles, key aroma compound quantification, and cluster analysis of 15 brands of extra-virgin olive oils (EVOOs) from three countries (Spain, Italy, and Greece) were investigated in the current study. Aroma compounds were isolated from the oil by using solvent-assisted flavor evaporation (SAFE) and solid-phase micro-extraction (SPME) and analyzed by gas chromatography-olfactometry mass spectrometry (GC-MS/O). A total of 89 compounds were screened by SPME/SAFE-GC-MS/O with chromatographic columns in 15 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 39 publications
(122 reference statements)
1
28
0
Order By: Relevance
“…Aldehydes usually predominate VOC profiles, a fact also confirmed in the current study (Table 2 , 35–42 mg/L), and significantly (due to low threshold values, OTV) positively contribute to aroma [ 3 , 70 ]. (E)-2-hexenal contribution, related to green and fruity attributes [ 6 , 71 ], is widely discussed as this is considered the most predominant and remarkable VOO VOC [ 3 , 6 , 21 ].…”
Section: Resultssupporting
confidence: 85%
“…Aldehydes usually predominate VOC profiles, a fact also confirmed in the current study (Table 2 , 35–42 mg/L), and significantly (due to low threshold values, OTV) positively contribute to aroma [ 3 , 70 ]. (E)-2-hexenal contribution, related to green and fruity attributes [ 6 , 71 ], is widely discussed as this is considered the most predominant and remarkable VOO VOC [ 3 , 6 , 21 ].…”
Section: Resultssupporting
confidence: 85%
“…C5 aldehydes and alcohols provide pungent sensations in correlation with bitterness [21]. Taking into account the information reported by numerous studies, it can be concluded that the C6 and C5 volatile compounds are powerful odorants, but they can be found in EVOO in a wide range of concentrations, according to differences in olive varieties and extraction methods applied [37].…”
Section: Flavor Compoundsmentioning
confidence: 99%
“…To give an example, in a study comparing the volatile compounds of EVOOs from different origins, it was observed that 6700 µg/g of trans-2-hexenal only have an odor activity of 16 whereas 26 µg/g of 1-penten-3-one had a higher odor activity value of 36 [36]. Regarding C5 compounds, they are also contained in EVOO in reasonable amounts, contributing to its flavor [37]. C5 aldehydes and alcohols provide pungent sensations in correlation with bitterness [21].…”
Section: Flavor Compoundsmentioning
confidence: 99%
“…Solvent‐assisted flavor evaporation (SAFE) is an efficient extraction method with high sensitivity, good repeatability, and allows low‐temperature extraction to protect the natural flavor compounds of food (Fricke & Schieberle, 2020; Majcher & Jelen, 2009). SAFE has been successfully applied in the extraction of volatile compounds from olive oil (Zhou et al., 2019), palm kernel oil (Zhang et al., 2016), and pumpkin seed oil (Poehlmann & Schieberle, 2013), but it has not been applied in sunflower seed oils.…”
Section: Introductionmentioning
confidence: 99%